2019
DOI: 10.3727/096504018x15202953107093
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Chemotherapy Following Surgical Resection Improves Survival in Patients With Early Stage Small Cell Lung Cancer

Abstract: The purpose of this study was to determine the effects of resection coupled with standard chemotherapy on survival prognosis of patients with early-stage small cell lung carcinoma (SCLC). Patients (n=110) with mediastinal lymph node-negative SCLC were enrolled in this study. The baseline clinical data of patients with surgery was retrospectively reviewed. Overall and progression-free survival were measured by Kaplan-Meier and log-rank test analyses. Ninety-eight patients received mediastinoscopy biopsy and pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
(3 reference statements)
0
9
1
Order By: Relevance
“…Through univariate and multivariate analysis, age, sex, surgery, T stage, LND, LNM, and chemotherapy were recognized as independent prognostic parameters, which was in high accordance with previous reports. 11,16,[21][22][23] Notably, radiotherapy was revealed not to be a significant prognostic factor in our study, which may be attributed to the contradictory impact of radiotherapy on patients with different N statuses. Wong et al 12 reported that radiotherapy deteriorated OS in N0 SCLC patients, but improved survival in N2-stage patients.…”
Section: Discussioncontrasting
confidence: 61%
“…Through univariate and multivariate analysis, age, sex, surgery, T stage, LND, LNM, and chemotherapy were recognized as independent prognostic parameters, which was in high accordance with previous reports. 11,16,[21][22][23] Notably, radiotherapy was revealed not to be a significant prognostic factor in our study, which may be attributed to the contradictory impact of radiotherapy on patients with different N statuses. Wong et al 12 reported that radiotherapy deteriorated OS in N0 SCLC patients, but improved survival in N2-stage patients.…”
Section: Discussioncontrasting
confidence: 61%
“…Furthermore, reports show that chemotherapy/ radiotherapy may be effective and could decrease the risk of recurrence in SCLC, and could provide a survival benefit to patients 26,27 . However, chemotherapy/radiotherapy alone is associated with poor prognosis when compared with surgery with adjuvant therapy for early stage SCLC 28,29 . These results support an increased role of surgery in the multimodality treatment of SCLC, and the combination of surgery with chemotherapy/ radiotherapy could be beneficial in patients with early stage SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PNENs have tumors sufficiently localized to be considered treatable by surgical resection, and among those whose tumors are successfully resected, approximately 90-98% of patients with typical carcinoid, and 50-60% of atypical carcinoid, survive 5 years ( 2 , 3 ) even developing local invasiveness, dissemination to regional lymph nodes, and distant metastasis ( 4 , 5 ) which occur in 3% of typical carcinoids and 21% for atypical carcinoids ( 6 8 ). In contrast, only 20-30% of the patients with large cell neuroendocrine carcinoma survive 5 years after surgical resection and adjuvant chemotherapy ( 9 ), and only 10% of the patients with small cell lung carcinoma survive 5 years after Cisplatin + Carboplatin + Etoposide ( 10 ).…”
Section: Introductionmentioning
confidence: 99%